Ken Yeager at Stanford University. - Sahl, Ted (photographer):::Creator::::::::::::
Portrait of Ken Yeager at Stanford University "Cares Day". Ken Yeager was later elected to San Jose City Council and to the Santa Clara County Board of Supervisors.